Health and Nutritional Status of Aged People (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Background: There is inadequate evidence based information to assist health policy makers in preparing for appropriate health, nutrition and social support guideline for the elderly in Bangladesh. Objective: The present study is an attempt to assess the health and nutritional status of elderly people in selected hospital in Dhaka.Methods: It was a cross sectional descriptive study. The subjects were selected purposively. The study was conducted among 50 elderly attending Bangabandhu Sheikh Mujib Medical University. Anthropometric data such as height and weight of the study subjects were collected by using standard techniques. Nutritional status was measured according to WHO guideline.Result: Most of the subjects belong to 60-64 yrs age group. Overall nutritional status as well as health status was not good and satisfactory. Most of them were suffering from malnutrition and arthritis as well as diabetes was very common. Partial reduced of appetite was seen among respondents. Dietary pattern was not good. Conclusion: Health and nutritional status of aged people in this study was not satisfactory.Recommendation: Intervention programs related to health and nutritional status may be arranged.DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i3.21019